2004
DOI: 10.7326/0003-4819-141-12-200412210-00011
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: Hepatobiliary Disease in Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus is the fifth leading cause of death in the United States; 17 million people are affected. Liver disease is one of the leading causes of death in persons with type 2 diabetes. The standardized mortality rate for death from liver disease is greater than that for cardiovascular disease. The spectrum of liver disease in type 2 diabetes ranges from nonalcoholic fatty liver disease to cirrhosis and hepatocellular carcinoma. The incidence of hepatitis C and acute liver failure is also increased. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
70
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 125 publications
1
70
0
3
Order By: Relevance
“…Hepatobiliary disorders, such as inflammation, necrosis or fibrosis of non-alcoholic fatty liver disease, cirrhosis, hepatocellular carcinoma, hepatitis C, acute liver failure, and cholelithiasis are complications of diabetes [6,7].Therefore combating diabetes mellitus goes far beyond mere glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatobiliary disorders, such as inflammation, necrosis or fibrosis of non-alcoholic fatty liver disease, cirrhosis, hepatocellular carcinoma, hepatitis C, acute liver failure, and cholelithiasis are complications of diabetes [6,7].Therefore combating diabetes mellitus goes far beyond mere glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a positive association between hepatitis C virus (HCV) infection and diabetes mellitus (DM) had been reported in a number of clinical studies [1][2][3][4] . It is now clear that hepatitis C conveys a risk for developing DM, in particular type 2 [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…By affecting glycogen and lipid metabolism, diabetes causes structural and functional abnormalities in the liver (6). Studies have shown that hepatobiliary disorders, such as infl ammation, necrosis and acute liver failure can follow diabetes (7,8).…”
Section: Introductionmentioning
confidence: 99%